Systematic Reviews - Lockwood, Craig; SpringerLink (Online service) (London : BioMed Central : Imprint: BioMed Central.)
The journal publishes high quality systematic review products including systematic review protocols, systematic reviews related to a very broad definition of human health, (animal studies relevant for human health), rapid reviews, updates of already completed systematic reviews, and methods research related to the science of systematic reviews, such as decision modelling. At this time Systematic Reviews does not accept reviews of in vitro studies. The journal also aims to ensure that the results of all well-conducted systematic reviews are published, regardless of their outcome. (You can now also prospectively register these reviews on PROSPERO.).
Keywords: Public health; Medicine$1 (BResearch.s; Biology$1 (BResearch.s; Biometry; Clinical medicine$1 (BResearch.s; Medicine; Medical care; Public Health; Biomedical Research; Biostatistics; Clinical Research; Clinical Medicine; Health Care